Fenomena Market Overreaction di Bursa Efek Indonesia (Management Analysis Journal, 2015)
This research examines the market overreaction in Indonesia Stock Exchange from 2009 to 2013. The population in this research are all of the companies that list in Indonesia Stock Exchange. The sample are stocks which are belonging to active stocks, it is determined by purposive sampling method. Market overreaction are measured by abnormal return and indicated with ACAR loser portfolio outperformed of ACAR winner portfolio. The result on quarterly period, semester period, and year period showed that loser portfolio outperformed winner portfolio. Value of the statistic tasting with one sample t test more than 0,05. This research concluded that there are market overreaction in Indonesia Stock Exchange and it’s not happens constantly